Obstetric outcome of teenage pregnancy in comparison with pregnant women of 20-29 years: a retrospective study - Nair, Atmaja; Devi, Sumangala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adolescent pregnancy also called as teenage pregnancy is a major public health problem worldwide. Adolescence is defined by WHO as a period from 10-19 years. Adolescent pregnancy results from a number of factors like early marriage, lack of education, premarital sexual relations and lack of awareness regarding contraception. The impact of adolescent pregnancy on the teenager and her future generation is disastrous. This includes obstetric complications like anemia, hypertensive disorders, preterm labour, still births and low birth weight babies. The objective of the present study was to compare the obstetric outcome of teenage pregnancy with that of pregnant women of 20-29 years age group. Methods: This was a hospital based retrospective case-control study conducted in a tertiary care teaching hospital in North Kerala from January 2013 to June 2013. Data collection was done from hospital records. The next delivery belonging to 20-29 years age group entered in parturition register after a teenage delivery was taken as control after satisfying inclusion and exclusion criteria. The obstetric outcome was recorded and analysed. Results: The incidence of teenage pregnancy during the study period was 8.48%. 90.89% of teenage pregnant women were primigravidae. 40.7% were anaemic, 18.22% had preterm labor, 14.87% had preeclampsia and 29.5% of the babies had low birth weight. Conclusions: Teenage pregnancy continues to be a major public health problem in India. The young age structure of Indian population favours more number of adolescents in the country. Preventing early marriages and delaying the onset of child bearing may go a long way in decreasing the number of teenage pregnancies.